A photocatalyst-free method for the synthesis of 6-alkyl(aryl)phenanthridines under visible light irradiation. (21st November 2022) - Natarajan, Palani; Partigya,; Pooja,
Abstract : The reaction was initiated by the photochemical activity of an electron donor–acceptor complex formed by the interaction of isocyanobiaryls with alkyl(aryl)sulfinates. Abstract : A novel and effective blue LED-induced methodology has been developed to synthesize a number of 6-alkyl(aryl)phenanthridines from isocyanobiaryls and alkyl(aryl)sulfinates in ethyl lactate under aerobic conditions. This protocol did not require a photoredox catalyst, and the reaction was sparked by the photochemical activity of an electron donor–acceptor complex formed by the interaction of isocyanobiaryls with alkyl(aryl)sulfinates. The environmental friendliness, mildness, gram-scale synthesizability, lack of toxic organic solvents/additives, and lack of a transition metal are only a few notable advantages of this methodology.